Analisis Efektifitas Jalur Sepeda Berdasarkan Metode Bicycle Level Of Service (BLOS) - Rohmadiani, Linda Dwi; Iskandar, Savira Ayu (Ge-STRAM: Jurnal Perencanaan dan Rekayasa Sipil, 2020)
The bicycle lane policy on the Darmo Highway - Urip Sumoharjo Street - Basuki Rahmat Street - Suryo Governor Street - Panglima Sudirman Street Surabaya City for 8,789 Km has been implemented since 2014. The width of the bicycle lane on this corridor of 1.5 meters is on the road body. The application of bicycle lanes in the city of Surabaya is still less effective because there are still many motor vehicle users, the lack of bicycle users and the purpose of cycling is only for recreation (car free day). The purpose of this study was to analyze the level of effectiveness of the bicycle lanes in the Basuki Rahmat Jalan Surabaya corridor. The method used is quantitative descriptive analysis technique Bicycle Level Of Service (BLOS). Data collection is done by survey and documentation. The results of the BLOS analysis that Monday, Saturday and Sunday BLOS value is "F" more than 5.5 means that the environment is not safe for bicycles except Sunday at 06.00-08.00 BLOS value is "D" means less environment for bicycles.